2019
DOI: 10.1177/2158244019835935
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies Through Secondary Students at Saudi School in Malaysia

Abstract: This study is dedicated to the research of vocabulary learning strategies (VLSs) employed by a group of Saudi Arabian learners in an EFL (English as a foreign language) context. The rationale for the study is to clarify a pronounced lack of research on the EFL context in Saudi Schools Abroad (SSA), and a dearth of prior research into VLSs in this context. In particular, this research intends to explore how do students at Saudi School Malaysia (SSM) employ VLSs in their actual learning process. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 18 publications
(21 reference statements)
3
25
1
Order By: Relevance
“…The findings of this study support the findings of the current study. Yaacob et al (2019) contrary to the findings of the current study, reported that the male students' level of using vocabulary learning strategies is higher than that of the female students.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study support the findings of the current study. Yaacob et al (2019) contrary to the findings of the current study, reported that the male students' level of using vocabulary learning strategies is higher than that of the female students.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, it can be argued that the 5 th and 6 th grade students' level of using vocabulary learning strategies in foreign language is higher than that of the 7 th graders. In a study conducted by Yaacob et al (2019) on the middle school students, it was found that with students' increasing grade level, their level of using vocabulary-learning strategies also increases. Thus, this finding reported in the literature does not concur with the finding of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a similar vein with the previous study, the participant of the present study employs affective strategies infrequently. Yaacob et al (2019) stated that in order to be successful in learning languages, in the learning strategies, a language learner must place the focus on vocabulary building rather than on memorizing grammar rules and structures. Referring to this belief, the participant in the present study had also shown more effort in vocabulary building.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, learners have focus attention, planning, organizing, arranging, monitoring, and evaluating the learning process (Oxford, 1990in Ardasheva & Tretter, 2013. The metacognitive strategies are related to students' own regulation and monitoring of their vocabulary learning (Yaacob, et al 2019). Affective strategies assist in regulating emotions, attitudes, motivation, and values.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before VLSs have had received much attention. Yaacob, Shapii, Saad Alobaisy, Al-Rahmi, Al-Dheleai, Yahaya, & Alamri (2019) examined vocabulary learning strategies employed by a group of Saudi Arabian learners in an EFL context. The results of this study revealed the percentage and frequency have further underscored this role and the significance of vocabulary learning in both students and teachers.…”
Section: Vocabulary Learning Strategiesmentioning
confidence: 99%